Health Education of Clean and Healthy Lifestyle using Card Telling Methods towards Diarrhea Prevention Among Children in Elementary School - Laila Mufida; Esti Yunitasari; Elida Ulfiana (Pediomaternal Nursing Journal, 2021)
Introduction:Diarrhea was one of the common diseases that easily acquired by school-age children. It is caused by a lack of health education about hygiene and health. Clean And healthy lifestyle education is one of the viable solutions to prevent diarrhea in elementary school-age children. The purpose of the research is to analyze the effect of health education hygiene and health behavior by using a card-telling method toward child elementary school-aged diarrhea prevention behavior.Methods: This study used a quasi-experimental design. The total number of respondents is 60 children. The respondents were recruited by purposive sampling method. The instrument of study is a card telling and modified the questionnaire adjacent to the previous study. The data were collected used questionnaires and observations than analyzed used significance of <0.05 Wilcoxon sign rank test and Mann-Whitney U test.Results: The Wilcoxon sign rank test result by using a card telling method has a total value p=0.000, then <0.05 there is the effect of the card telling method on hygiene and health behavior to preventing diarrhea knowledge, attitude, and action of the child elementary school age. The statistical analysis showed differences in post-test results between the control group and the treatment group with p=0.000.Conclusion: The card telling method could increase the level of knowledge, attitude, and skill of the child elementary school age. The nurse could use a card telling to achieve optimal results in giving the health education of children.